Placental LEP Promoter Hypomethylation is Associated with Increased Leptin and Umbilical Artery Vascular Resistance in Maternal Obesity - Fridsto, Zeino; Serudji, Joserizal; Defrin, Defrin; Hardisman, Hardisman (The Indonesian Biomedical Journal, 2026)
BACKGROUND: Maternal obesity has been associated with altered fetal development involving metabolic, hormonal, vascular, and epigenetic processes. The leptin (LEP) gene is crucial for placental angiogenesis and fetal growth. However, evidence linking placental LEP promoter methylation status with both leptin levels and umbilical artery vascular resistance in the context of maternal obesity remains limited. Therefore, this study was conducted to investigate the association of placental LEP promoter hypomethylation with increased leptin levels and umbilical artery vascular resistance in maternal obesity.METHODS: A cross-sectional study was conducted in 35 obese and 35 normal-body mass index (BMI) pregnant women delivering at term. Genomic DNA was extracted from placental tissue for the placental LEP promoter methylation examination using bisulfite conversion and CpG pyrosequencing. Umbilical artery systolic/diastolic (S/D) ratio was measured by Doppler ultrasonography, and umbilical cord leptin levels were analyzed from umbilical cord blood using enzyme-linked immunosorbent assay (ELISA).RESULTS: Total LEP promoter methylation did not differ significantly between groups (p=0.252), but five CpG sites (CpG 5, 11, 13, 16, and 17) showed significant hypomethylation in the obesity group. Umbilical cord leptin levels were significantly higher in infants of obese mothers (p=0.002). The S/D ratio was also significantly higher in the obesity group (p<0.001), indicating increased placental vascular resistance. Maternal age, parity, and gestational age were comparable between groups.CONCLUSION: Placental LEP promoter hypomethylation at specific CpG sites (CpG 5, 11, 13, 16, and 17) in maternal obesity is associated with increased leptin levels and elevated umbilical artery vascular resistance, suggesting a potential epigenetic mechanism linking maternal obesity to placental vascular dysfunction and altered fetal development.KEYWORDS: maternal obesity, leptin, DNA methylation, placenta, umbilical artery Doppler, fetal programming